EFISIENSI GADGET SEBAGAI MEDIA PEMBELAJARAN BAGI SISWA SD DI KELURAHAN SEKAR MAWAR KABUPATEN INDRAGIRI HULU - Andri Sulistyani; Dian Ardi Pratiwi; Delvia Agustina; Dira Radianti; Irvan Agustria Wana; Nur Asikin; Rama Novriano; Rika Arianti; Risti Maydita Winanda; Sefrilia Resty; Vonni Dea Pratiwi (COVIT (Community Service of Health), 2022)
The purpose of the journal is to provide broader knowledge regarding Gadget Efficiency as a learning media for primary school students in Sekar Mawar Sub-District, Indragiri Hulu Regency. the use of gadgets such as tablets in the classroom can contribute to an increase in student performance, it can also contribute to a decrease in the number of students who perform poorly in class. Not only that, gadgets also help improve the efficiency of teaching methods and students' learning capacity using tablets in class. Overall, the use of electronic gadgets has made the activities carried out in the classroom more flexible. Activities carried out by Kukerta students included conducting socialization related to the efficiency of gadgets as learning media for elementary students at SDN 003 Sekar Mawar regarding the meaning of gadgets, kinds of gadgets, positive and negative impacts of gadgets, how to use gadgets well, guidelines for using Google Meet, Zoom and Google Classroom as technology-based learning media using gadgets. Furthermore, Kukerta Students conducted a quiz with prizes which were asked to students of SDN 003 Sekar Mawar about the material described in the socialization, the last activity carried out was direct practice in using Zoom, Google Classroom, and Google Meet. Keywords: Gadgets, Benefit, Learning Media